Microbial biomass, organic colloids and inorganic nitrogen, during vermicomposting of some substrates - de Aquino, Adriana Maria; de Almeida, Dejair Lopes; Guerra, José Guilherme Marinho; De-Polli, Helvécio (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objetive of this work was to evaluate modifications in the microbial biomass, metabolic quotient, types of mineral nitrogen, C/N ratio, and total organic colloids concentration. The following variations in the substrate composition were utilized: pure cattle manure, pure cattle manure + sugarcane bagasse 1:1 ratio, and pure cattle manure + sugarcane bagasse + leaves of Cajanus cajan 2:1:1 ratio. The mixture was made on volume bases and the substrate composition filled boxes of 0.4 m3. Three hundred earthworms of the species Eisenia foetida and 100 of Eudrillus eugeniae were introduced in the boxes. Every 20 days, approximately, samples were collected for analysis during a total period of 126 days. The experiment was placed in a randomized complete block design, with a factorial 3x8, with three replications and the following treatments: three types of substrate and eight sampling dates. Microbial biomass, metabolic quotient and types of mineral nitrogen concentrations were not good indexes to characterize the maturity point of the vermicomposting process. Based on C/N ratio, the pure cattle manure reached stability in 70 days and sugarcane bagasse and pure cattle manure + sugarcane bagasse + Cajanus cajan leaves in 90 days. The determination of organic colloids was a simple assay, but was not also a good index to characterize the maturity point of the vermicomposting process.